“Penumbra sign” in knee pain: a case of distal femur osteomyelitis - Hakan Koray Tosyali; Adem Çakir (Brazilian Journal of Medical and Biological Research, 2024)
“Penumbra sign” is a characteristic finding in magnetic resonance imaging (MRI) of Brodie's abscess, a rare variant of subacute osteomyelitis. We aimed to discuss the imaging finding penumbra sign that will help in the diagnosis of osteomyelitis and may be useful to clinicians in differential diagnosis. A 26-year-old male patient presented to the emergency department with complaints of pain and limping in the right knee that did not go away. He had a history of arthroscopic debridement and percutaneous fixation surgery due to osteochondral fragment 3 years ago. There were no additional findings in the patient's vital parameters, physical examination, and medical history. X-ray imaging revealed two screws in the distal femur and a well-defined sclerotic rim surrounding a radiolucent lesion anterior to the screws. MRI revealed a lesion in the distal femoral metaphysis with low-density fluid and hyperintense granulation tissue surrounding it. After surgical abscess drainage and local debridement, bone cement was placed in the resulting cavity. Teicoplanin treatment was started. The patient was discharged and complete recovery was achieved in the second month. The diagnosis of osteomyelitis is often missed or confused with bone tumors in non-traumatic cases presenting with persistent bone pain. MRI imaging is frequently used in differential diagnosis, and detection of characteristic imaging signs such as the penumbra sign accelerates the diagnosis. In this context, emergency department clinicians, in particular, should be cautious and not forget that early treatment can be started by recognizing these signs.